Quantum Computing:A possibility to find COVID-19 antidote - Sonal, Deepa (International Journal of Computer Sciences and Engineering, 2020)
Today, the whole world is suffering from pandemic of Covid-19 diseases. Corona virus disease 2019 (COVID- 19) is an illness caused by a novel coronavirus now called as severe acute respiratory syndrome coronavirus 2 (SARSCoV-2; formerly called 2019-nCoV), which was first identified amid an outbreak of respiratory illness cases in Wuhan City, Hubei Province, China. Today, every country in the world is trying to find the antidote of COVID-19. Meanwhile, a hope to find the medicine of Covid-19, can be seen through Quantum Computing. For the readers who are not familiar with quantum computation, a brief introduction to it is provided. Classical computers that are used today can encode information only in binary format that take the values of 1 or 0. This restricts the ability of classical computers. On the opposite hand, Quantum computing is a region of computing that deals with developing engineering supported the principles of scientific theory, that explains the behavior of energy and material at the atomic and subatomic levels. Quantum computing uses quantum bits or qubits. it's the distinctive ability of subatomic participles that enables them to exist in additional than one states i.e. one and zero at an equivalent time. These supercomputers area unit supported by Superposition and entanglement, 2 vital options of physics. Quantum computing relies on the principles of scientific theory and uses the quantum-mechanical phenomena like superposition and entanglement to perform computations.